2014
DOI: 10.5897/ajmr2014.6668
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens associated with infectious diarrhea in King Khalid University Hospital, Riyadh Saudi Arabia 2005-2010

Abstract: Diarrhoeal diseases are major cause of morbidity worldwide. In developed and developing countries, Salmonella, Shigella and Campylobacter species are the main bacterial causes. This study aimed to investigate the occurrence and antimicrobial susceptibility of bacteria causing diarrhea in Riyadh, during a six years period. This study was performed in Riyadh capitol of Saudi Arabia between January 2005 to December 2010. The data was obtained from request forms for stool examination of patients complaining of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Five kinds of viruses are considered relevant as a cause of gastroenteritis including rotaviruses, adenoviruses, noroviruses, astrovirus, and bocavirus (Silva et al, 2008 ). Bacterial pathogens come as the second common causes of diarrhea in developing countries, and such bacteria include Escherichia coli, Shigella spp., Campylobacter spp., Salmonella spp., and Vibrio parahaemolyticus (Somily et al, 2014 ; Wang et al, 2014 ). However, in sporadic cases of adult diarrhea Vibrio cholerae, Yersinia, Shigella, and Salmonella spp., are the most common causative agents in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Five kinds of viruses are considered relevant as a cause of gastroenteritis including rotaviruses, adenoviruses, noroviruses, astrovirus, and bocavirus (Silva et al, 2008 ). Bacterial pathogens come as the second common causes of diarrhea in developing countries, and such bacteria include Escherichia coli, Shigella spp., Campylobacter spp., Salmonella spp., and Vibrio parahaemolyticus (Somily et al, 2014 ; Wang et al, 2014 ). However, in sporadic cases of adult diarrhea Vibrio cholerae, Yersinia, Shigella, and Salmonella spp., are the most common causative agents in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…There was however a significant association (p= 0.0003) of the isolation of Campylobacter with the presentation of diarrhoea in children aged 0-24 months in this study. Other studies including those that were carried out by Rathaur et al (2014) and Somily et al (2014) have shown that Campylobacter species are often isolated alongside other enteric pathogens. This study further corroborates these reports as other bacterial pathogens were co-isolated with Campylobacter in every case in which this organism was associated with diarrhoea.…”
Section: Discussionmentioning
confidence: 96%